Formação permanente de professores no cotidiano escolar: o real e o possível - Souza, Geruza Ferreira Ribeiro de (2022)
This research aims to understand the meanings attributed to permanent education among peers in school routine. Starting from the main objective and using experiences lived by teachers, we carried out this qualitative research with a(n) (auto) biographical approach, through conversation circle and narratives in which teachers ponder on their development and individual and collective training movements. The narrative interviews took place with six teachers of Elementary School I in the municipal system of Feira de Santana-Ba. The work is anchored in the contributions of several authors, especially Freire, Nóvoa, Pineau, Rios, Silva, Gatti, Imbernón and Larossa. Studies revealed formative singularities and showed that even in the face of legislative limitations and struggles between conquered and instituted times, there is a training potential to be carried out with thoughtful collective participation, with teachers being protagonists of their training from their own practices in school routine, with special emphasis on collective movements in Complementary Activities. Among many results, voices echoed from teachers attributing meaning to training as a permanent movement of learning to teach in school routine, following principles of peer qualification, time-space, ability to dialogue, collaboration, among others.